PERANAN SISTEM INFORMASI DALAM MENINGKATKAN EFISIENSI DAN EFEKTIVITAS PENYIARAN DI RADIO DANGDUT INDONESIA (RDI) SEKAYU - Tores, Ropal; Devi, Charitin (Jurnal Ilmu Manajemen, 2017)
This research aimed to know the role of information system in increasingbroadcasting effectivity and efficiency at Radio Dangdut Indonesia (RDI)Sekayu. This research was done by using Field research, that is thereseachers directly came to Radio Dangdut Indonesia office to makeinterview to the employees who have authorized to give information that isneeded and Library research that is collecting data was done by thereseachers by reading all reference books those related to the title andobserved problems in order to get theories those can be used as availabledata analysis tool materials. This research result showed that the role ofcomputer based Management information system has proved to be able tosupport broadcasting effectivity and efficiency at Radio Dangdut IndonesiaSekayu. This research gave the newest evidence related to informationsystem roles in increasing effectivity and efficiency of broadcasting at RadioDangdut Indonesia (RDI) Sekayu.